In-situ profiling of glycosylation on single cells with surface plasmon resonance imaging - Xiaoyin Liu; Jinbiao Ma; Yunrui Zhang; Yi Xu; Yunxiao Wang; Dehong Yang; Di Wang; Qingjun Liu; Fenni Zhang (Nature Communications)
Abstract Cellular glycosylation is crucial for cell recognition, signal transduction, and the development of various diseases, especially in tumor initiation, progression, and metastasis. Current glycosylation profiling methods normally involve laborious sample processing and labeling and lack in-situ quantitative analysis. Here, we present a direct optical method to investigate and quantify the glycan expression on single cells based on lectin-glycan kinetic quantification with plasmonic imaging. Three unlabeled lectins (WGA, SBA, ConA) are employed as probes to bind with specific glycans, and binding kinetics are assessed to determine glycosylation profiles. The result reveals cell-to-cell heterogeneity in glycosylation patterns. To demonstrate the capability of our method, the glycosylation profiling of four distinct cell lines is explored, showing obvious alterations in glycan expression related to tumor initiation, progression, and metastasis. This approach enables direct quantification of glycosylation and binding kinetics, providing insights into tumor cell glycosylation mechanisms and potential applications in disease diagnosis and treatment.